Use of Reclaimed Water for Irrigation in Container Nurseries - Tom Yeager; Claudia Larsen; Joe von Merveldt; Tracy Irani (EDIS, 2009)
ENH-1119, an 8-page illustrated fact sheet by Tom Yeager, Claudia Larsen, Joe von Merveldt, and Tracy Irani, informs container nursery producers about irrigating with water processed from municipal sewage wastewater, the results of evaluations of overhead sprinkler irrigation systems, where to get it, and special application procedures and cautions. Includes references and a glossary. Published by the UF Department of Environmental Horticulture, May 2009.